2019
DOI: 10.1088/1742-6596/1399/5/055016
|View full text |Cite
|
Sign up to set email alerts
|

Research of high-speed diesel engines of small dimension on biofuel

Abstract: The paper substantiates the need for the use of biofuels in diesel engines. It is shown that the choice for diesel alternative biofuel with a perspective should be carried out in accordance with the design features of the engine and during its primary tests. The paper studies such eco-friendly energy sources as methanol, ethanol and methyl ether of rapeseed oil. Methanol, ethanol and methyl ester of rapeseed oil potentially lead to some solutions to environmental problems, as for their production, there are qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Cara pembuatan bioetanol dari berbagai bahan baku dan proses pembuatannya metanolisis minyak rapeseed dipertimbangkan. Studi eksperimental biodiesel beroperasi pada emulsi bahan bakar alkohol, metanol, dan metil eter minyak lobak dilakukan [90].…”
Section: Research Of High-speed Diesel Engines Of Small Dimension On ...unclassified
“…Cara pembuatan bioetanol dari berbagai bahan baku dan proses pembuatannya metanolisis minyak rapeseed dipertimbangkan. Studi eksperimental biodiesel beroperasi pada emulsi bahan bakar alkohol, metanol, dan metil eter minyak lobak dilakukan [90].…”
Section: Research Of High-speed Diesel Engines Of Small Dimension On ...unclassified
“…Studies of the efficiency of the engine fueled with vegetable fuels showed changes in the engine's operating parameters, including an increase in fuel flow resistance, an increase in fuel density, a decrease in engine power and a decrease in overall engine efficiency [13,14,15]. Based on research on fuel consumption, an increase in the demand for fuel can be seen [16,17,18]. Fuel consumption, with the use of a 35% addition of fatty acid methyl esters to diesel fuel, increases by about 18% compared to pure diesel fuel [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Hence biodiesel, among the biofuel candidates, have been in high-speed research and commercialization in recent years. [4][5][6] This has led to the largescale accumulation of glycerol, a byproduct of the transesterification reaction for biodiesel synthesis. 7 Recent reports have shown that over 2.4 million tons of glycerol is produced per year in the EU, which exceeds the required amount for the entire world.…”
Section: Introductionmentioning
confidence: 99%